2021
DOI: 10.1523/jneurosci.1605-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Associative Learning Requires Neurofibromin to Modulate GABAergic Inputs to Drosophila Mushroom Bodies

Abstract: Cognitive dysfunction is among the hallmark symptoms of Neurofibromatosis 1, and accordingly, loss of the Drosophila melanogaster ortholog of Neurofibromin 1 (dNf1) precipitates associative learning deficits. However, the affected circuitry in the adult CNS remained unclear and the compromised mechanisms debatable. Although the main evolutionarily conserved function attributed to Nf1 is to inactivate Ras, decreased cAMP signaling on its loss has been thought to underlie impaired learning. Using mixed sex popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 60 publications
1
27
1
Order By: Relevance
“…These findings raise the possibility that sleep dysregulation is due to altered GABA signaling. Supporting this notion, GABA signaling to the mushroom bodies, the Drosophila memory center, is dysregulated in Nf1 mutants (Georganta et al, 2021). It has also previously been reported that Nf1 knockdown in GABA A receptor neurons leads to shortened sleep bouts and reduced sleep duration (Maurer et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These findings raise the possibility that sleep dysregulation is due to altered GABA signaling. Supporting this notion, GABA signaling to the mushroom bodies, the Drosophila memory center, is dysregulated in Nf1 mutants (Georganta et al, 2021). It has also previously been reported that Nf1 knockdown in GABA A receptor neurons leads to shortened sleep bouts and reduced sleep duration (Maurer et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Taken together, loss of Nf1 results in sleep fragmentation, reduced arousal threshold, and loss of sleepdependent changes in metabolic rate, suggesting that Nf1 is required for flies to enter deep sleep. While Nf1 is broadly expressed throughout the brain, its function has been linked to the modulation of GABA signaling during the formation of associative memories (Georganta et al, 2021). In Drosophila, the GABAA receptor Resistant to dieldrin (Rdl) is expressed in numerous populations of sleep-regulating neurons (Fig 4A; Chung et al, 2009;Driscoll et al, 2021;Parisky et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirroring Nf1- mutant mouse findings, dNf1 loss results in increased GABAergic signaling and disrupted associative learning. Importantly, learning is not restored following pharmacologic cAMP restoration, indicating that GABAergic signaling occurs independently of cAMP/PKA signaling in dNf1 -mutant flies ( Georganta et al, 2021 ). Together, these observations reveal RAS-cAMP-dependent long-term memory and RAS-cAMP-independent short-term memory functions of neurofibromin in Drosophila neurons.…”
Section: Neurofibromin and Non-canonical Ras Pathway Signalingmentioning
confidence: 99%
“…circuits (He et al, 2019;Liu et al, 2020), learning and memory circuits (Scaplen et al, 2020;Georganta et al, 2021), and circuits controlling aggression (Hu et al, 2020;Wu et al, 2020), social attraction (Sun et al, 2020), and circadian rhythm and sleep (Guo et al, 2018;Dreyer et al, 2019;Liu et al, 2019;Duhart et al, 2020). It has also been applied to identify neuropeptide synapses (Zandawala et al, 2018(Zandawala et al, , 2021 and other neuronal targets, such as the adipose tissue (Scopelliti et al, 2019).…”
Section: Applications Of Genetic Transsynaptic Toolsmentioning
confidence: 99%